PENDEKATAN NARATIF DALAM PRAKTIK PEKERJAAN SOSIAL UNTUK MENGATASI TRAUMA KEKERASAN DALAM RUMAH TANGGA - br. Sitepu, Badikenita (Jurnal Insani, 2024)
The narrative approach in social work practice is an effective intervention strategy to help victims of domestic violence (DV) recover their identity and rebuild their meaning after experiencing trauma. This study aims to analyze the application of the narrative approach in the context of social work as an effort to recover from trauma caused by domestic violence. This approach starts from the assumption that a person's life experience is constructed through narratives or stories told about themselves and their environment. Through the process of "re- authoring" (rewriting their life story), social workers help victims separate themselves from the dominant narrative filled with guilt, fear, and helplessness, towards a new narrative that emphasizes strength, resilience, and hope. The method used is a descriptive qualitative study that examines empirical and theoretical literature related to the application of narrative therapy in social practice. The results of the analysis indicate that the narrative approach allows victims to express traumatic experiences safely, identify new meanings of suffering, and develop adaptive coping strategies. In addition, social workers act as facilitators of critical reflection that encourages empowerment and the reconstruction of a positive identity. Inconclusion, the narrative approach serves not only as a therapeutic technique but also as an ethical and relational framework for social work practice that focuses on individual dignity, autonomy, and empowerment. Therefore, this approach is highly relevant in supporting the holistic recovery of domestic violence victims and strengthening trauma-informed and social justice social work practices.